Synthesis and In Vitro Antimycobacterial Activity of Novel N-Arylpiperazines Containing an Ethane-1,2-diyl Connecting Chain - Goněc, Tomáš; Malík, Ivan; Csöllei, Jozef; Jampílek, Josef; Stolaříková, Jiřina; Solovič, Ivan; Mikuš, Peter; Keltošová, Stanislava; Kollár, Peter; O'Mahony, Jim; Coffey, Aidan (Molecules (Basel, Switzerland), 2017)
Novel 1-(2-{3-/4-[(alkoxycarbonyl)amino]phenyl}-2-hydroxyethyl)-4-(2-fluorophenyl)-piperazin-1-ium chlorides (alkoxy = methoxy to butoxy; 8a-h) have been designed and synthesized through multistep reactions as a part of on-going research programme focused on finding new antimycobacterials. Lipophilic properties of these compounds were estimated by RP-HPLC using methanol/water mobile phases with a various volume fraction of the organic modifier. The log kw values, which were extrapolated from intercepts of a linear relationship between the logarithm of a retention factor k (log k) and volume fraction of a mobile phase modifier (ϕM), varied from 2.113 (compound 8e) to 2.930 (compound 8h) and indicated relatively high lipophilicity of these salts. Electronic properties of the molecules 8a-h were investigated by evaluation of their UV/Vis spectra. In a next phase of the research, the compounds 8a-h were in vitro screened against M. tuberculosis CNCTC My 331/88 (identical with H37Rv and ATCC 2794), M. kansasii CNCTC My 235/80 (identical with ATCC 12478), a M. kansasii 6 509/96 clinical isolate, M. avium CNCTC My 330/80 (identical with ATCC 25291) and M. avium intracellulare ATCC 13950, respectively, as well as against M. kansasii CIT11/06, M. avium subsp. paratuberculosis CIT03 and M. avium hominissuis CIT10/08 clinical isolates using isoniazid, ethambutol, ofloxacin, ciprofloxacin or pyrazinamide as reference drugs. The tested compounds 8a-h were found to be the most promising against M. tuberculosis; a MIC = 8 μM was observed for the most effective 1-(2-{4-[(butoxycarbonyl)amino]phen-ylphenyl}-2-hydroxyethyl)-4-(2-fluorophenyl)piperazin-1-ium chloride (8h). In addition, all of them showed low (insignificant) in vitro toxicity against a human monocytic leukemia THP-1 cell line, as observed LD50 values > 30 μM indicated. The structure-antimycobacterial activity relationships of the analyzed 8a-h series are also discussed.
Keywords: hydrofobní a hydrofilní interakce; nádorové buněčné linie; N-arylpiperazines; Mycobacterium tuberculosis; Mycobacterium tuberculosis H37Rv; lipophilicity; Cell Line, Tumor; Microbial Sensitivity Tests; spektrální analýza; Hydrophobic and Hydrophilic Interactions; Antitubercular Agents; vztahy mezi strukturou a aktivitou; Humans; Molecular Structure; Piperazines; viabilita buněk; Cell Survival; molekulární struktura; arylaminoethanols; Spectrum Analysis; mikrobiální testy citlivosti; piperaziny; Structure-Activity Relationship; lidé; electronic properties; antituberkulotika